Improved Methane Sensing Properties of Co-Doped SnO2 Electrospun Nanofibers. (13th November 2013) - Chen, Weigen; Zhou, Qu; Xu, Lingna; Wan, Fu; Peng, Shudi; Zeng, Wen
Abstract : Co-doped SnO2 nanofibers were successfully synthesized via electrospinning method, and Co-doped SnO2 nanospheres were also prepared with traditional hydrothermal synthesis route for comparison. The synthesized SnO2 nanostructures were characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy, and X-ray photoelectron spectra. Planar-type chemical gas sensors were fabricated and their sensing properties to methane were investigated in detail. Gas sensors based on these two samples demonstrate the highest CH4 sensing response at an operating temperature of 300°C. Compared with traditional SnO2 nanospheres, the nanofiber sensor shows obviously enhanced gas response, higher saturated detection concentration, and quicker response-recovery time to methane. Moreover, good stability, prominent reproducibility, and excellent selectivity are also observed based on the nanofibers. These results demonstrate the potential application of Co-doped SnO2 nanofibers for fabricating high performance methane sensors.